The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.5751/es-01847-120106
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Social Capital and Conflict Management in Multiple Resource Regimes: A Case of the Southwestern Highlands of Uganda

Abstract: Increasingly, social capital, defined as shared norms, trust, and the horizontal and vertical social networks that facilitate coordination and cooperation for mutually beneficial collective action, is seen as an important asset upon which people rely to manage natural resources and resolve conflicts. This paper uses empirical data from households and community surveys and case studies, to examine the role, strengths, and limits of social capital in managing conflicts over the use and management of natural reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 17 publications
(16 reference statements)
1
69
0
10
Order By: Relevance
“…For example, during the collective period, it was the responsibility of the communes and of the banner governments to organize and help herders to conduct otor when natural disasters occurred, which greatly reduced animal losses (Xie andHuntsinger 2011). Other studies have also shown that governments can play active roles in natural resource management by mediating conflicts that extend beyond the community level (Sanginga et al 2007), by solving the problems of resource capture by certain elites (Sanginga et al 2007), and by remedying inadequate informal sanctions (Bowles and Gintis 2002) within communities. Therefore, we argue that it does not matter whether government interference is strong or weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during the collective period, it was the responsibility of the communes and of the banner governments to organize and help herders to conduct otor when natural disasters occurred, which greatly reduced animal losses (Xie andHuntsinger 2011). Other studies have also shown that governments can play active roles in natural resource management by mediating conflicts that extend beyond the community level (Sanginga et al 2007), by solving the problems of resource capture by certain elites (Sanginga et al 2007), and by remedying inadequate informal sanctions (Bowles and Gintis 2002) within communities. Therefore, we argue that it does not matter whether government interference is strong or weak.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, external factors have increasingly dominated livestock breed improvement and management in Inner Mongolia. There has been general agreement in the research literature on common pool resource management that external interventions should be adapted to the needs of the target system, and should not crowd out and displace the original cooperative relationships that existed within the system and the human community, and that the relationship between governments and local communities should be complementary instead of displacing existing social structures (Agrawal and Gibson 1999, Bowles and Gintis 2002, Sanginga et al 2007. Unfortunately, in the process of livestock breed improvement in the Inner Mongolian rangeland SES, the original relationships within the system have been increasingly disrupted by external factors.…”
Section: How Interventions Come Into Effectmentioning
confidence: 99%
“…Common tie characteristics are those of importance, frequency, or intensity. Several studies distinguish between bonding, bridging, and linking ties (Sanginga et al 2007, Bodin and Crona 2008, Ramirez-Sanchez and Pinkerton 2009, Stein et al 2011, Cohen et al 2012, Marín et al 2012, 2015, Sundstrom et al 2012, Cárcamo et al 2014, Apgar et al 2015. Few studies highlight the influence of network context (Tompkins et al 2002, Rico García-Amado et al 2012, Sundstrom et al 2012 or actor characteristics, such as leadership or socioeconomic power (Bodin andCrona 2008, Crona andBodin 2010) to explain agency or lack thereof.…”
Section: Network Operationalizationmentioning
confidence: 99%
“…Network approach: Structurally explicit approaches, and in particular the application of SNA techniques, are characteristic of most studies in this strand, however, there are also studies that refer to social networks in metaphorical terms, treating networks as an binary variable (Tompkins et al 2002, Sanginga et al 2007, Gelcich et al 2010, Sundstrom et al 2012). …”
Section: Network Operationalizationmentioning
confidence: 99%
See 1 more Smart Citation